Phenotypic data for M. edulis responses to warming and ocean acidification - Matoo, Omera; Lannig, Gisela; Bock, Christian; Sokolova, Inna (Dryad, 2021)
1. In mosaic marine habitats, such as intertidal zones, ocean
acidification (OA) is exacerbated by high variability of pH, temperature,
and biological CO2 production. The non-linear interactions among these
drivers can be context-specific and their effect on organisms in these
habitats remains largely unknown, warranting further investigation. 2. We
were particularly interested in Mytilus edulis (the blue mussel) from
intertidal zones of the Gulf of Maine (GOM), USA for this study. GOM is a
hot spot of global climate change (average Sea Surface Temperature (SST)
increasing by > 0.2 °C y−1 ) with > 60% decline in mussel
population over the past 40 years. 3. Here, we utilize bioenergetic
underpinnings to identify limits of stress tolerance in M. edulis from GOM
exposed to warming and OA. We have measured whole-organism oxygen
consumption rates and metabolic biomarkers in mussels exposed to control
and elevated temperatures (10 vs. 15 °C, respectively) and current and
moderately elevated PCO2 levels (~ 400 vs. 800 µatm, respectively). 4. Our
study demonstrates that adult M. edulis from GOM are metabolically
resilient to the moderate OA scenario but responsive to warming as seen in
changes in metabolic rate, energy reserves (total lipids), metabolite
profiles (glucose and osmolyte dimethyl amine) and enzyme activities
(carbonic anhydrase and calcium-ATPase). 5. Our results are in agreement
with recent literature that OA scenarios for the next 100-300 years do not
affect this species, possibly as a consequence of maintaining its in vivo
acid−base balance.
Keywords: FOS: Biological sciences